DEVELOPMENT MODEL OF UNDER DEVELOPED SMALL ISLAND IN SUMENEP - Sudarti Sudarti; Zainal Arifin; Sutikno Sutikno (Economic Journal of Emerging Markets, 2010)
The purpose of this study is to build a Geographic Information System and Management Information System models of development of small islands in Sumenep. Based on the identification of economic potential there are few regions such as Nonggunong, Gayam, Ra'as, and Sapeken which have large contribution toward the rice plant production. The whole districts of the islands in Sumenep are the base of cow, horse, chicken and livestock commodities. Sapeken have significant contribution for marine fish. Giligenting, Nonggunong, Gayam, and Arjasa have large potential for brackish fish. Moreover, Gili-genting also has a great contribution for fresh fish.Keywords: Development model, under-developed area, small islandsJEL classification numbers: O13, O14